Social Learning and Natural Resource Management: The Emergence of Three Research Perspectives - and Rodela, Romina (Ecology and Society, 2011)
Rodela, R. 2011. Social learning and natural resource management: the emergence of three research perspectives. Ecology and Society 16(4): 30. https://doi.org/10.5751/ES-04554-160430